Análisis de preconceptos sobre velocidad y rapidez en estudiantes de primer semestre de licenciatura en física, Universidad Distrital Francisco José de Caldas - Pedraza, Andres Fernando; Sánchez, Malory Johana (Revista Científica, 2011)
﻿Preconceived mental structures in which the student articulates the world are of vital importance in the development of a new cognitive device. Thus, it seeks from two basic concepts in the fields of kinematics realize a study of two basic concepts in the area of kinematics on previous ideas in the first semester students belonging to the career degree in physics from the Universidad Distrital Francisco José de Caldas through the classroom use computer simulations of two tours, in order to diagnose the kind of conceptualization that has the group.